Peningkatan Hasil Belajar Pendidikan Pancasila Peserta Didik Menggunakan Model Cooperative Learning Tipe STAD di Kelas IV Sekolah Dasar - Ranti Satriani Putri; Muhammadi Muhammadi (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The purpose of the study is to describe the use of the STAD Type Cooperative Learning model to improve student learning outcomes in Pancasila Education learning in grade IV of Elementary School. This research is a Classroom Action Research (CAR) with a qualitative and quantitative approach carried out in two cycles. The subjects in this study were teachers and students of grade IV/B students of SDN 23 Painan Utara. Data sources are teaching modules, student and teacher observation results, and student learning outcomes using techniques in the form of observation and testing. The results of observations of the implementation of learning modules in cycles I to II increased from 93.75% to 100%, the results of observations of teacher activities increased in cycles I to II, namely 92.86% to 100%, the results of observations of student activities increased in cycles I to II, namely 91.07% to 100%, as well as observations of student learning outcomes assessments, the average value increased from 83.77 to 93.86. It can be concluded that the STAD model can improve student learning outcomes in Pancasila Education in class IV of SDN 23 Painan Utara.